2006
DOI: 10.1111/j.1365-4632.2006.02593.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of desmoglein enzyme‐linked immunosorbent assay (ELISA) in Indian patients with pemphigus vulgaris

Abstract: ELISA (dsg1 and dsg3) is an efficient tool for confirming the diagnosis of PV. Specific antibody titers correlate with disease severity; however, desmoglein testing cannot differentiate between the various morphologic subtypes of PV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 13 publications
10
68
3
1
Order By: Relevance
“…Only patients with a "classical" antibody profile (IIF + and anti-Dsg3 + in PV, IIF + and anti-Dsg1 + in PF, at least once during the course of the disease) were included in our study. Epidemiological data and antibody profiles of our patients were comparable to previous reports (2,22,(36)(37)(38)(39)(40), except for one female patient who presented with erosive, crusted, vegetating plaques exclusively on her scalp, but negative anti-Dsg1 values. Based on histological findings (suprabasal acantholysis), ELISA values (Dsg1 -/Dsg3 + ), and immunoprecipitation (single band at 130 kDa, consistent with Dsg3) we favoured the diagnosis of a cutaneous type PV (22,41), reminiscent of a previously published case described as Dsg1 -/ Dsg3 + pemphigus vegetans of the scalp (42), but lacking histological changes typical for this variant of PV such as papillomatosis, acanthosis and an abundance of eosinophils (43).…”
Section: Discussionsupporting
confidence: 87%
“…Only patients with a "classical" antibody profile (IIF + and anti-Dsg3 + in PV, IIF + and anti-Dsg1 + in PF, at least once during the course of the disease) were included in our study. Epidemiological data and antibody profiles of our patients were comparable to previous reports (2,22,(36)(37)(38)(39)(40), except for one female patient who presented with erosive, crusted, vegetating plaques exclusively on her scalp, but negative anti-Dsg1 values. Based on histological findings (suprabasal acantholysis), ELISA values (Dsg1 -/Dsg3 + ), and immunoprecipitation (single band at 130 kDa, consistent with Dsg3) we favoured the diagnosis of a cutaneous type PV (22,41), reminiscent of a previously published case described as Dsg1 -/ Dsg3 + pemphigus vegetans of the scalp (42), but lacking histological changes typical for this variant of PV such as papillomatosis, acanthosis and an abundance of eosinophils (43).…”
Section: Discussionsupporting
confidence: 87%
“…In our previous study also we observed that the ELISA test could not differentiate between the various clinical phenotypes of PV because both anti-Dsg 1 and 3 titers were raised in all the three variants. [12] Jamora et al reported a high anti-Dsg 1 titer in 28% of mucosal PV and its absence in 29% of the cutaneous variant. [13] Delmonte et al reported raised anti-Dsg 1 antibody in 62% of PV.…”
Section: Discussionmentioning
confidence: 98%
“…Anti-Dsg 3 titer correlated positively with mucosal severity of the disease, while anti-Dsg 1 titers correlated with skin surface area involvement. [23] Pemphigus being an autoimmune disease driven by autoantibody against epidermal antigen, it is expected from immunological point of view that Th2 predominance would be observed. It has been confirmed by Satyam et al in their study on serum samples from patients of either PV or PF.…”
Section: Genetic Susceptibility and Immunological Aspectmentioning
confidence: 99%